Unusual osteochondral fracture of the second metatarsal head in a paediatric patient treated with bioabsorbable pin. Issue 2 (4th February 2021) - Umer, Hafiz Muhammad; Iqbal, Hafiz Javaid; Thonse, Raghuram
Abstract : Osteochondral second metatarsal head fractures are rare. Various management options have been described in the published literature. We used bioabsorbable pin (Activa Pin) system for our case of second metatarsal head fracture. This method not only achieves good compressive fixation, it also eliminates the risk of implant-related issues such as implant irritation. To our knowledge, no such paediatric case managed with this technique has been published in the literature.